Phylogenetics and phylogeography of red deer mtDNA lineages during the last 50 000 years in Eurasia. Zoological Journal of the Linnean Society - Doan, K.; Niedzialkowska, M.; Sykut, M.; Jędrzejewska, B.; Ratajczak-Skrzatek, U.; Piotrowska, N.; Ridush, B.; Stefaniak, K. (Oxford Academic, 2022)
The present phylogeographic pattern of red deer in Eurasia is not only a result of the contraction of their distribution range into glacial refugia and postglacial expansion, but probably also an effect of replacement of some red deer s.l. mtDNA lineages by others during the last 50 000 years. To better recognize this process, we analysed 501 sequences of mtDNA cytochrome b, including 194 ancient and 75 contemporary samples newly obtained for this study. The inclusion of 161 radiocarbon-dated samples enabled us to study the phylogeny in a temporal context and conduct divergence-time estimation and molecular dating. Depending on methodology, our estimate of divergence between Cervus elaphus and Cervus canadensis varied considerably (370 000 or 1.37 million years BP, respectively). The divergence times of genetic lineages and haplogroups corresponded to large environmental changes associated with stadials and interstadials of the Late Pleistocene. Due to the climatic oscillations, the distribution of C. elaphus and C. canadensis fluctuated in north–south and east–west directions. Some haplotypes dated to pre-Last Glacial Maximum periods were not detected afterwards, representing possibly extinct populations. We indicated with a high probability the presence of red deer sensu lato in south-eastern Europe and western Asia during the Last Glacial Maximum.
Keywords: ancient DNA; Cervus elaphus; cytochrome b; Holocene; Last Glacial Maximum; Late Pleistocene; mtDNA; phylogenetic; phylogeography; postglacial recolonization